2021
DOI: 10.1111/are.15439
|View full text |Cite
|
Sign up to set email alerts
|

Nanoselenium versus bulk selenium as a dietary supplement: Effects on growth, feed efficiency, intestinal histology, haemato‐biochemical and oxidative stress biomarkers in Nile tilapia ( Oreochromis niloticus Linnaeus, 1758) fingerlings

Abstract: Five isonitrogenous (30% crude protein) diets were formulated to contain two forms of selenium (Se): convention Se named Bulk‐Se or Se nanoparticles (Nano‐Se), both forms of Se supplemented at two levels 0.4 and 0.8 mg kg−1 diet compared to the control diet without addition for a period of 84 days. Nile tilapia, Oreochromis niloticus, fingerlings (5.0 ± 0.2 g) fed tested diets in triplicates at a rate of 5% of their total biomass three times a day for 84 days. The results showed that the best growth performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 69 publications
1
18
0
Order By: Relevance
“…Accordingly, the beneficial bacteria can perform more effectively in digesting the nutrients through the secretion of digestive enzymes. The enhancement in the growth performance of fish is also explained by Ibrahim et al [5], who indicated that Nile tilapia-fed dietary Se nanoparticles (0.4-0.8 mg/kg) showed enhanced growth performance and feed efficiency. The authors also confirmed that Se nanoparticles caused a positive impact on the intestinal histomorphological features.…”
Section: The Role Of Selenium Nanoparticles On the Growth Performancementioning
confidence: 61%
See 4 more Smart Citations
“…Accordingly, the beneficial bacteria can perform more effectively in digesting the nutrients through the secretion of digestive enzymes. The enhancement in the growth performance of fish is also explained by Ibrahim et al [5], who indicated that Nile tilapia-fed dietary Se nanoparticles (0.4-0.8 mg/kg) showed enhanced growth performance and feed efficiency. The authors also confirmed that Se nanoparticles caused a positive impact on the intestinal histomorphological features.…”
Section: The Role Of Selenium Nanoparticles On the Growth Performancementioning
confidence: 61%
“…Aquatic animals suffer from various biotic and abiotic stressors that may occur during the farming season [76]. Nutritionally balanced aquafeed is the main key factor that helps counteract these stressors leading to high productivity and well-being [5]. Microelements, including Se, is another vital strategy to guarantee the balance of the nutritional value of aquafeed [1].…”
Section: Effect Of Selenium Nanoparticles On the Immunological Biochemical And Hematological Parameters Of Bloodmentioning
confidence: 99%
See 3 more Smart Citations